Pengaruh Komitmen Organisasi, Kepuasan Kerja, Pembelajaran Organisasi, dan Motivasi Kerja Terhadap Kinerja Guru di XYZ School Karawaci - Vivi Jingga (Jurnal Ketopong Pendidikan, 2022)
Teacher plays an important role in determining the development and progress of a music school. In a music school, teacher directly deals with the students one by one as well as the parents. Teacher is then responsible for the progress of each students and reports the learning progress to the parents. It can be said that the teacher is the core that is very important for the progress of a music school. Therefore, teacher’s performance should be highly regarded based on the enormous role of teachers. This study aims to determine the effect of organizational commitment, job satisfaction, organizational learning, and work motivation on teachers’ performance in XYZ School Karawaci. with the subjects of research are thirty teachers. The research design used is Structural Equation Modeling (SEM) with quantitative approach. The results obtained showed that organizational commitment and job satisfaction affects the teachers’ performance positively as well as organizational learning and work motivation.